Hospital admissions into paediatric palliative care: A retrospective study - Íñigo de Noriega; Marta Barceló; María Ángeles Pérez; Verónica Puertas; Alberto García-Salido; Ricardo Martino (Elsevier, 2020)
Introduction: Patients may be admitted to hospital by paediatric palliative care units (PPCU) for different reasons, due to their different needs and clinical problems. The objective of this study is to present the data of patients admitted to the PPCU of the Autonomous Community of Madrid. Methods: Descriptive retrospective study was conducted by reviewing the clinical records of the PPCU between January 2011 and December 2016. Results: Of 499 patients attended in this period, 166 (33%) were admitted to hospital at some point, generating a total of 314 episodes. Respiratory problems (34%) were the main cause of admission. Gastrostomy intervention (23 patients) was the commonest reason for a surgical admission. In this period, 46 patients died during hospitalisation. The highest frequencies of death, according to the admission cause, were respiratory problems (18 out 46) and end-of-life care (11 out 46). More than half (59%) of admissions lasted less than 7 days and 88% were 15 days or less. Conclusions: The causes and characteristics of the hospital admissions at a PPCU are heterogeneous, with respiratory problems being the most common cause of admission. The duration of the hospitalisation appears to be similar to that described for acute palliative care units. The creation of a specific PPCU that can refer their patients for hospital admission might help to improve continuity of care. Resumen: Introducción: Los pacientes en seguimiento por unidades de cuidados paliativos pediátricos (UCPP) pueden ingresar en el hospital por distintas circunstancias. Cuentan con características dispares en sus necesidades y en las situaciones clínicas que presentan. El objetivo de este estudio es presentar datos correspondientes a los pacientes ingresados a cargo de la UCPP de la Comunidad Autónoma de Madrid. Métodos: Estudio retrospectivo observacional realizado a partir de las historias clínicas de la UCPP. Periodo: enero-2011 a diciembre-2016. Resultados: De los 499 pacientes seguidos en ese periodo, 166 (33%) ingresaron en alguna ocasión, generando un total de 314 episodios. El principal motivo de ingreso fueron los problemas respiratorios (34%). El motivo más frecuente de ingreso para intervención quirúrgica fue la realización de una gastrostomía (23 pacientes). En este periodo, 46 pacientes fallecieron durante el ingreso, siendo el motivo más frecuente el ingreso por problemas respiratorios (18/46), seguido de los ingresos por agonía (11/46). El 59% de los ingresos duró menos de 7 días y el 88%, 15 días o menos. Conclusiones: Los motivos y las características de los ingresos hospitalarios a cargo de una UCPP son heterogéneos, siendo los motivos más frecuentes los problemas respiratorios. La duración de la estancia hospitalaria es equiparable a la de unidades de cuidados paliativos de atención aguda. La creación de unidades específicas con posibilidad de ingreso hospitalario a cargo de las mismas puede ayudar a mantener la continuidad asistencial.